Post-Islamism and the Rise of Sharia Laws in Contemporary Indonesia: Aspirations of Implementing Islamic Laws in a Democratic Era - Bani Syarif Maula (International Journal of Social Science and Religion (IJSSR), 2023)
Islamism is an ideology and a movement that seeks to build an Islamic order in the form of an Islamic state and the enforcement of sharia law. However, in Indonesia during the democratization period in the early 2000s, many Islamic organizations, including Islamic parties and Islamic movements, liberated themselves from hiding and even opened their organizational philosophies to accommodate wider issues and concerns. While retaining their Islamic identity, some Islamic groups are turning towards the secularization of their goals and objectives as a means of adapting to the changing political environment. Political analysts refer to this development as post-Islamism. This change in attitude is to some extent due to the fact that Islamic legal institutions have become more prominent since the reform era. While retaining their Islamic identity, Islamic groups are turning towards the secularization of their goals and objectives as a means of adapting to the new political environment and changing the agenda of most Islamic political movements by way of Islamizing Indonesian values. That's why the color of legislation in Indonesia is more Islamic.